A complaint is a gift : how to learn from critical feedback and recover customer loyalty - Barlow, Janelle, 1943- (Berrett-Koehler Publishers, Inc., 2022)
The third edition of this bestseller (over 275,000 copies sold) builds on the tested formula that helps organizations recognize the value of complaints using updated examples and concepts in the age of COVID-19.